Fear of re-injury and other intrinsic factors are associated with return to sport after anterior cruciate ligament reconstruction - Ross, Cheryl Anne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScPhysio)--Stellenbosch University, 2015.